PELAKSANAAN MONITORING, EVALUASI, DAN PELAPORAN UNTUK PENILAIAN KINERJA MANAJERIAL KEPALA SEKOLAH - Wartomo Wartomo; Hotni Sari Harahap (JGK (Jurnal Guru Kita), 2022)
Implementation of Monitoring, Evaluation, and Reporting for Principal Managerial Performance Assessment. The purpose of this study was to determine the implementation of monitoring, evaluation, and reporting for assessing the managerial performance of school principals. The research approach uses a qualitative design through a modified analytical induction multi-site case study. The source of the research data were the principals of 20 elementary schools in Wirobrajan District, Madia City, Yogyakarta. Data was collected through observation, documentation and interviews. Resource persons were interviewed and involved in group discussion forums. The presence of researchers in the midst of a research setting is a must because researchers in qualitative research activities are the key instrument for capturing meaning. Data analysis was carried out in a qualitative descriptive research process. The results of the study indicate that several obstacles need to be removed in the implementation of monitoring, evaluation, and reporting for assessing the managerial performance of school principals.